Cultivar discrimination at different site elevations with remotely sensed vegetation indices - Bruno Basso; Davide Cammarano; Giovanni Cafiero; Stefano Marino; Arturo Alvino (Italian Journal of Agronomy)
The objectives of this study are (i) to evaluate vegetation indices sensitivity to discriminate between two different cultivars; (ii) to determine the effects of site elevation and developmental stages on cultivar discrimination. The experiment was carried out for the growing season 2007/08 at “Agro di Pesche” (Central Italy, Molise region). Four experimental fields were located at different elevation ranging between 590 m to 922 m above the sea level (asl). For each field, two potato (Soluanum Tuberosum L.) cultivars were used. Leaf area was collected through non-destructive measurements, and a hand-held spectroradiometer was used to measure the reflected light from the canopy of the two cultivars. Results from the ANOVA show that the ratio between MCARI (Modified Chlorophyll Absorption Ratio Index) and OSAVI (Optimized Soil Adjusted Vegetation Index), NDRE (Normalized Difference Red Edge) and MCARI were able to discriminate among cultivars at different site elevations. NDVI (Normalized Difference Vegetation Index) was not able to discriminate the two cultivars because of the influence of soil reflectance and leaves distribution.